Calcium phosphate stability on melt electrowritten PCL scaffolds - Abbasi, Naghmeh (H. : ĐHQGHN, 2020)
Calcium phosphate (CaP) coating on melt electrowritten (MEW) substrates is a potential candidate for bone regeneration influencing the interaction of osteoblasts with implanted scaffolds. Pretreatment to improve hydrophilicity of the hydrophobic polymer fibres affects subsequent coating with bioactive compounds like CaP. Therefore, this study evaluated the subsequent stability and structural properties of CaP coated MEW Poly-ε-caprolactone (PCL) scaffolds following pre-treatment with either argon-oxygen plasma or sodium hydroxide (NaOH). Scanning electron microscopy and m-CT showed uniform CaP coating after one hour immersion in simulated body fluid following plasma pretreatment. Moreover, fourier transform infrared spectroscopy, energy dispersive spectrometry and X-ray diffraction analysis confirmed the presence of hydroxyapatite, tetracalcium phosphate and halite structures on the coated scaffolds. Contact angle measurement showed that the plasma pretreatment and CaP coating improved the hydrophilicity of the scaffold. However, the mechanical properties of the scaffolds were degraded after both plasma and NaOH treatments. The tensile stability was significantly improved following mineralization in plasma-treated scaffolds due to the smaller crystal size formed on the surface resulting in a dense CaP layer. The results obtained by thermogravimetric analysis also confirmed higher deposition of CaP particles on coated scaffolds following plasma modification. The results of this study show that plasma pre-treated mineralized MEW PCL scaffolds are sufficiently stable to be useful for further development in bone regeneration applications.